Seawaves in the Qur’anic Perspective - Busaeri Busaeri; Nurwadjah Ahmad; Harmain Ajiwibowo (Jurnal Iman dan Spiritualitas, 2022)
The development of science contains an invitation to humankind to think, read the universe, and contemplate all the secrets contained in His creation. Scientific cues in the Qur'an show evidence of Allah's oneness and infinite power. There is not a single creation of Allah that is not useful or useless, including the phenomenon of wave terms in the Qur'an. This term in the Qur'an is intended as a negative connotation, a wave that causes extraordinary and frightening destructive power. The research is on the waves from the Qur’anic perspective with thematic approaches. The results of this study show that: first, the sea waves in the Qur'an are called the word al-mauj (الْمَوْجُ) and their derivation is repeated 7 times in Surah Yunus [10]:22, Hud [11]:43, Al-Kahf[18]:99, Hud[11]:42, Lukman [31]:32 and Al-Nur[24]:40 which means اج البحر (moving sea water) which means water the sea up and down, then used in the word اج القوم (group movement) which means they are in dispute over their affairs and problems, then the word اج الحق (movement from the right). The Qur'an refers to two meanings: the movement of seawater in the letters Lukman [31]:32 and Al-Nur[24]:40, the second refers to the movement carried out by a group in the letter. Al-Kahf[18]:99, which refers to Gog and Magog. Second, sea waves in the Qur'an can be proven in scientific studies, including that waves are vibrations that propagate in seawater with several layers that cause waves, the influence of the wind as the driving force of the waves, the presence of internal (deep sea) waves.